2020
DOI: 10.1002/qre.2606
|View full text |Cite
|
Sign up to set email alerts
|

Improving the ARL profile and the accuracy of its calculation for Poisson EWMA charts

Abstract: The Poisson exponentially weighted moving average (PEWMA) chart was proposed in 1998 by Borror, Champ, and Rigdon to monitor the mean of counts of nonconformities. This chart regrettably fails to have an in‐control average run length (ARL) larger than any out‐of‐control ARL, ie, the PEWMA chart is ARL‐biased. Moreover, due to the discrete character of its control statistic the PEWMA chart and the resulting subtleties of its ARL calculation, it is difficult to set the control limits in such way that the in‐cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Table 4: Optimal combinations (λ * , K * ) and corresponding out-of-control ARL values for p 0 ∈ {0.05, 0.1, 0.15, 0.2}, τ ∈ {1.1, 1.2, 1.5, 2} and σ ∈ {0.1, 0.125, 0.15, 0.2} for the upper-sided BEWMA chart with "continuousify" in an efficient way. Finally, a comparison with the recent "Splitting Markov Chain" approach proposed by Morais and Knoth (2020) has shown that our "continuousify" method performs in a similar way in the case of the PEWMA control chart.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Table 4: Optimal combinations (λ * , K * ) and corresponding out-of-control ARL values for p 0 ∈ {0.05, 0.1, 0.15, 0.2}, τ ∈ {1.1, 1.2, 1.5, 2} and σ ∈ {0.1, 0.125, 0.15, 0.2} for the upper-sided BEWMA chart with "continuousify" in an efficient way. Finally, a comparison with the recent "Splitting Markov Chain" approach proposed by Morais and Knoth (2020) has shown that our "continuousify" method performs in a similar way in the case of the PEWMA control chart.…”
mentioning
confidence: 72%
“…It is interesting to note that this topic (efficient ARL computation for EWMA control charts monitoring discrete data) has also grasped the attention of other researchers and, very recently, Morais and Knoth (2020) have proposed an alternative method called the "Splitting Markov Chain". This approach has been applied to a two-sided PEWMA control chart (while, in this paper, we investigate a max-type upper sided PEWMA control chart).…”
Section: The "Continuousified" Upper-sided Pewma Chartmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Abbasi 16 developed Poisson progressive mean (PPM) charts under the zero and steady-state situations. The interested readers are referred to Rakitzis et al, 17 Morais et al, 18 Cabral Morais and Knoth, 19 Abbas et al, 20 and Aly et al 21 for more literature on Poisson charting schemes.…”
Section: Introductionmentioning
confidence: 99%
“…A new PEWMA chart is introduced by Sukparungsee [18] improved based on square transformation of Poisson data. In considering PEWMA as ARL-biased, Morais and Konth [19] used the Markov chain to determine ARL accurately and compared some competing results of previous studies. Although the Poisson distribution is frequently used to describe count data, it assumes that variance is equal to the mean (equi dispersion), which could lead to incorrect inferences in the case of overdispersion [20].…”
Section: Introductionmentioning
confidence: 99%